Pengaruh Trust, Word of Mouth Dan Repurchase Intention Terhadap Kepuasan Pelanggan Generasi Millennial Produk Minuman Street Boba - Devi Yusiana Fitri; Puspita Chairun Nisa (Jurnal Ecodemica : Jurnal Ekonomi Manajemen dan Bisnis, 2022)
This study was conducted to determine whether the price promotion precursors, brand image, product quality, and value obtained affect the satisfaction of millennial generation customers. And to determine the effect of customer satisfaction on trust, word of mouth, and repurchase intention. The contribution of this research is expected to add information at the theoretical or scientific level of marketing management and also to provide implications in marketing on business management. The study used a survey method as a data collection technique, and a questionnaire as an instrument and distributed both to the target population of the millennial generation between the ages of 17 to 39 years with the research area in Bekasi and focusing on samples who had bought street boba drinks. The sample used in the study amounted to 185 respondents, quantitative research with data processing methods used were Smartpls and SPSS. (1) price promotions, and brand image, do not affect millennial generation customer satisfaction in consuming them. (2) product quality has a positive but not significant effect, the value obtained has a positive and significant effect on customer satisfaction. (3) customer satisfaction with trust, word of mouth, and repurchase intention has a positive and significant effect Keywords: customer satisfaction, trust, word of mouth, repurchase intention